2020
DOI: 10.3390/molecules25235580
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Allergic Potential of Cinnamaldehyde via the Inhibitory Effect of Histidine Decarboxylase (HDC) Producing Klebsiella pneumonia

Abstract: Allergy is an immunological disorder that develops in response to exposure to an allergen, and histamines mediate these effects via histidine decarboxylase (HDC) activity at the intracellular level. In the present study, we developed a 3D model of Klebsiella pneumoniae histidine decarboxylase (HDC) and analyzed the HDC inhibitory potential of cinnamaldehyde (CA) and subsequent anti-allergic potential using a bacterial and mammalian mast cell model. A computational and in vitro study using K. pneumonia revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…In this study, RLE was demonstrated to act on the mRNA and protein expression of HDC–the sole enzyme that functions in histamine production from histidine ( Figure 8 ). The pharmacological study reported that mRNA and protein expression of HDC was inhibited by mitogen-activated protein kinase (MEK) and c-Jun terminal kinase inhibitor, demonstrating that the MAPK pathway plays a significant role in the transduction of inhibitory signals to suppress HDC expression [ 25 ]. The results suggested that the regulatory mechanism of RLE on HDC was mediated by downregulating MAPK signaling, consequently exerting the activity of transcription factors of the HDC gene, including GATA2, MITF, SP1, and KLF4 ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, RLE was demonstrated to act on the mRNA and protein expression of HDC–the sole enzyme that functions in histamine production from histidine ( Figure 8 ). The pharmacological study reported that mRNA and protein expression of HDC was inhibited by mitogen-activated protein kinase (MEK) and c-Jun terminal kinase inhibitor, demonstrating that the MAPK pathway plays a significant role in the transduction of inhibitory signals to suppress HDC expression [ 25 ]. The results suggested that the regulatory mechanism of RLE on HDC was mediated by downregulating MAPK signaling, consequently exerting the activity of transcription factors of the HDC gene, including GATA2, MITF, SP1, and KLF4 ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…20 For this reason, experimental evidence has postulated that cinnamon reduced the degranulation of MCs, thereby regulating histamine synthesis. 21 It is thought that cinnamon plays an essential role in the intracellular mobilization of Ca ++ ions in mucosal MCs with its inhibitory effects on the phospholipase C signaling pathway. 18 Consistent with these studies, our findings showed that cinnamon extract reduced the increase in liver MCs number induced by STZ.…”
Section: Groupsmentioning
confidence: 99%
“…C. cassia is also widely used in traditional Chinese medicine. Cinnamaldehyde, one of the most important bioactive ingredients in C. cassia , has beneficial effects, such as antibacterial, 13 anti-allergic, 14 anti-inflammatory 15 and anticancer effects. 16 Our previous study indicated that ethanoic C. cassia extracts suppresses cell invasion by repressing matrix metalloproteinase-2 and u-PA and reverses TGF-β1-induced EMT by up-regulating E-cadherin in human lung adenocarcinoma cells.…”
Section: Introductionmentioning
confidence: 99%